Передопераційна оптимізація волемічного статуса у пацієнтів з ожирінням - Воротинцев, Сергій Іванович; Воротынцев, С. И.; Vorotyntsev, S. І. (Полтава: Українська медична стоматологічна академія, 2018)
Резюме. Передопераційна оптимізація венозного повернення крові до серця та її адекватний об’єм є особливо важливими у пацієнтів з ожирінням для запобігання періопераційної циркуляторної нестабільності. В дослідженні був оцінений вплив внутрішньовенного об’ємного навантаження (ОН) Геласпаном з розрахунку 6 мл/кг від ідеальної маси тіла (ІдМТ) на ударний об’єм серця (УО) та індекс загального судинного опору (ІЗСО) у 26 пацієнтів з ожирінням перед лапароскопічною хірургією, та визначена інцидентність передопераційної гіпотензії (ПОГ) у них після індукції загальної анестезії. Виявлено, що ОН призвело до зростання УО більш ніж на 13% від вихідного рівня у 19 (73%) пацієнтів без клінічних ознак гіперволемії (p<0,05), а ПОГ зафіксована у 4 (15%) пацієнтів (p<0,05) на тлі 22% зниження ІЗСО, порівняно з ІЗСО після ОН (p<0,05). Таким чином, режим ОН Геласпаном 6 мл/кг ІдМТ є адекватним та безпечним для передопераційної оптимізації волемічного статуса у пацієнтів з ожирінням, що забезпечує майже 50% зниження ризику ПОГ та опосередковано підтверджує наявність у них вихідної гіповолемії. Резюме. Предоперационная оптимизация венозного возврата крови к сердцу и ее адекватный объем являются особенно важными у пациентов с ожирением для предупреждения периоперационной циркуляторной нестабильности. В исследовании было оценено влияние внутривенной объемной нагрузки (ОН) Геласпаном из расчета 6 мл/кг от идеальной массы тела (ИдМТ) на ударный объем сердца (УО) и индекс общего сосудистого сопротивления (ИОСС) у 26 пациентов с ожирением перед лапароскопической хирургией, и определена инцидентность предоперационной гипотензии (ПОГ) у них после индукции общей анестезии. Выявлено, что ОН привела к росту УО больше чем на 13% от исходного уровня у 19 (73%) пациентов без клинических признаков гиперволемии (p<0,05), а ПОГ зафиксирована у 4 (15%) пациентов (p<0,05) на фоне 22% снижения ИОСС, в сравнении с ИОСС после ОН (p<0,05). Таким образом, режим ОН Геласпаном 6 мл/кг ИдМТ является адекватным и безопасным для предоперационной оптимизации волемического статуса у пациентов с ожирением, что обеспечивает почти 50% снижение риска ПОГ и косвенно подтверждает наличие у них исходной гиповолемии. Abstract. Obesity is a risk factor for many perioperative complications, cardiovascular in particular, that most often occur when hemodynamics is unstable. It is proved that hypotension occurs more often in patients with obesity during induction of anaesthesia. This is due to initial hypovolemia in 70% of patients with morbid obesity who are preparing for bariatric surgery with help of the program for weight loss. But publications related to the regime of fluid therapy for non-bariatric patients with increased BMI, especially with a focus on preoperative treatment, are few and not based on general consensus. The aim of our work was to evaluate the effect of preoperative individualized according to the ideal body weight (IBW) volume loading by fluid (VL) on hemodynamic parameters and to determine the incidence of preoperative hypotension (POH) during the use of VL in obese patients. The research included 26 obese patients (BMI>30 kg/m2) that were planned for scheduled laparoscopic surgery and to whom the dynamics of the stroke volume of the heart (SV) and the index of systemic vascular resistance (SVRI) were measured using impedance measurement after VL by balanced colloid (Gelaspan, BBraun, Germany) at a rate of 6 ml/kg IBW in addition to standard monitoring of hemoglobin saturation (SpO2), noninvasive mean arterial pressure (MAP) and heart rate (HR). The research was conducted in awake patients immediately before the induction of anesthesia. They were classified as volume-respondents if SV increased by more than 13% from the initial level. After induction of anesthesia (diazepame 1.25-2.5 mg, fentanyl 1-1.5 mg/kg IBW, atracurium 0.4 mg/kg LBW (lean body weight), propofol 1-2 mg/kg of LBW, ketamine 0.15 mg/kg IBW) but before the operation any decrease of BP by more than 20% from the basic level was considered as hypotension. The incidence of POH and the mean level of MAP were compared with retrospective data in a group of obese patients to whom VL by colloid according to above methodology was not conducted. Statistical analysis was provided with a program Statistica for Windows version 6.0. The mean calculated volume of loading was 456±62 ml of Gelaspan. 19 (73%) patients had a response to VL as an increase of SV>13% (p<0.05). At the same time values of HR, MAP and SVRI did not significantly change. After induction of anesthesia POH appeared in 4 (15%) of patients with the mean level of MAP minimum value 57±12 mm Hg. In all patients SVRI decreased to 1780±235 din/cm×sec-5 (p<0.05) and in patients with POH – reached a value of 1400±210 din/cm×sec-5 (p<0.05). Retrospective analysis of 68 anesthetic charts revealed POH in 27 (25%) patients (p <0.05). So, we found that volume loading mode by colloid 6 ml/kg of IBW is adequate and safe for preoperative optimization of volemic status in obese patients that provides almost 50% reduction in the risk of hypotension after induction of general anesthesia and indirectly confirms a status of output hypovolemia in them.
Предоперационная оптимизация волемического статуса у пациентов с ожирением
Preoperative optimization of the volemic status in patients with obesity
Keywords: ожиріння; лапароскопічна хірургія; волемічний статус; ожирение; лапароскопическая хирургия; волемический статус; obesity; laparoscopic surgery; volemic status